MANAGING COMPANY’S FOREIGN CURRENCY LOAN TO INCREASE PERFORMANCE THROUGH ECONOMIC VALUE ADDED - Manurung, Elizabeth Tiur (TRIKONOMIKA, 2019)
One impact of global crisis, is increasing foreign currency rate of Indonesian IDR. Company with foreign debt exposures will suffer financial losses, if the exchange rate of the foreign currency becomes stronger. These losses will reduce the company Economic Value Added (EVA), and reduce the financial performance. Then, the purpose of this research is to calculate the effect of changes in foreign currency rates on the company’s economic value added. Research method used in this study is Causal method. This study used company secondary data, based on Indonesian Stock Exchange. Based on research conducted, the result of this research proves that the changes in foreign currency rates on foreign liabilities affected significantly (with α = 5%) on company’s economic value added. In PT. KF case, revenues earned by the company could cover all cost incurred including cost to cover the loss of exchange rate gap of foreign debt and capital cost